Root exudates: The rhizospheric frontier for advancing sustainable plant protection - Muhammad Rahil Afzal; Misbah Naz; Youbo Yu; Lisha Yan; Peiyi Wang; Janaki Mohotti; GeFei Hao; Jing-Jiang Zhou; Zhuo Chen; Libo Zhang; Qian Wang (Resources, Environment and Sustainability)
Root exudates (REs), a diverse array of bioactive metabolites secreted by plant roots in response to environmental stimuli, serve as key mediators of rhizosphere ecology and plant defense responses, offering a promising avenue for sustainable pest management and eco-friendly plant protection. While earlier reviews primarily focus on root exudates in the context of general rhizosphere dynamics and plant-microbial interactions, critical knowledge gaps persist in REs-plant-pest tripartite interactions, the mechanistic basis of REs-mediated plant defense, and their practical integration with integrated pest management (IPM) frameworks. This review provides a synthesis of the latest literature on the biochemical diversity and functions of REs, their environmentally-driven exudation dynamics, and their roles in induced systemic resistance (ISR) in plants and disrupting pest communication and development. Furthermore, we highlight their translational potential-including advances in RE-inspired green pesticide development, and emerging strategies that employ beneficial microorganisms to modulate REs profile for enhanced plant protection. By integrating these insights, this review underscores the potential of REs to redefine modern pest management strategies. We advocate for interdisciplinary research to further explore the ecological and evolutionary roles of REs, ultimately contributing to more resilient and sustainable agricultural systems.